Evidence that the liquid structure affects the nucleation of the primary metastable L12-Al3Zr in additive manufacturing. (15th March 2023) - Buttard, Maxence; Martin, Guilhem; Harrison, Patrick; Rauch, Edgar F.; Chéhab, Béchir; Jarry, Philippe; Blandin, Jean-Jacques; Donnadieu, Patricia
Abstract: The strategy aiming at promoting the precipitation of the primary metastable L12 -Al3 X phase is the most widely used to refine grain size in Al alloys designed for additive manufacturing. It is generally admitted that Al grains nucleate onto the primary L12 -Al3 X precipitates by epitaxy resulting in a cube-cube orientation relationship. Here we report TEM observations showing clusters of precipitates of this primary L12 -Al3 X phase. Using Automated Crystallographic Orientation Mapping in the TEM, we show that such clusters consist of various orientations. Analysis of those clusters reveals that some orientations share common 5-fold rotational symmetry axes suggesting that they have nucleated from an icosahedral template. We conclude that Icosahedral Short Range Order (ISRO) in the liquid can play a role in the nucleation of the primary metastable L12 -Al3 Zr phase through the ISRO-mediated nucleation mechanism. Graphical abstract: Image, graphical abstract